PENGARUH PENAMBAHAN BUAH SAWO MENTEGA (POUTERIA CAMPECHIANA) TERHADAP KANDUNGAN GIZI, AKTIVITAS ANTIOKSIDAN, DAN SIFAT ORGANOLEPTIK MI KERING - Irna Ghafira (2023)
Dried noodles is an Indonesians' favorite dish, apparently the food itself contains a small amount of antioxidant. Previous studies suggest by consuming rich-antioxidant foods could decrease the amount of stress oxidative in the body. Canistel (Pouteria campechiana) contains antioxidants and potentially useful for dried noodles material. The purpose of this study is to comprehend the nutrition values, antioxidant activity, and organoleptic of canistel dried noodle. The proportion of canistel fruit (CF) and wheat flour (WF) were investigated at ratio 15% CF : 85% WF, 30% CF : 70% WF, 45% CF : 55%WF. The data were analyzed with Kruskall Wallis and Mann Whitney for organoleptic. One Way Analysis of Variance (ANOVA) and Duncan Multiple Range Test (DMRT) were use for proximate analysis and antioxidant activity. Based on the data results, there are significant differences of the addition of canistel (Pouteria campechiana) on dried noodles' antioxidant activity (0,035<0,05), color and texture of canistel dried noodle (0,000<0,05). Canistel dried noodle with the most liked by panelists is F3 product which contains 378,9 kcal; 2,9 g fat; 12,1 g protein; 76,05 g carbohydrate; and antioxidant activity level 6,709.78 ppm per 100 g.